Hazel Shelton: capstone - Shelton, Hazel, artist (Colorado State University. Libraries, 2025)
The artist's statement: I make paintings of landscapes and the beings that inhabit them. I am inspired by dreams, almost-too-close observations of the world around me, weird animals, the unloved and weird and otherwise underappreciated (be it worms or people), and multispecies theory. My paintings are celebrations of the sentience of their inhabitants and how our proximity to them changes us. They are meditations on questions like what might happen if we spend time close to a particularly insightful Gila monster – even if she never shares what she knows. As I paint, I am interested in creating feelings that defy easy categorization. At the simplest level, I invite strangeness. While strangeness can feel uncomfortable, I have found it also pairs well with good humor and curiosity. I approach painting with an interest in the materials I am using, constantly experimenting with techniques and recognizing the materials' agency as I work with – and sometimes against – them. I love the endless approaches you can take with oil paint, and how it invites chaos at every turn. With enough solvent, thick paint becomes fractals that slip unpredictably down the face of the canvas. Inevitably, the paint finds its way onto surfaces that have never been close to a palette. Oil paint creates a web of mess that offers only one solution: keep painting.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting